Use of MIMICS® software in three-dimensional cephalometric evaluation of soft tissues of the face. Issue 1 (2nd January 2017) - Mazzoli, Alida; Antonio, Gracco; Masi, Angela; Siciliani, Giuseppe
Abstract : The main limitations connected to the traditional diagnostic techniques of imaging in orthodontics are that they offer a 2D representation of 3D structures. Given that facial harmony has become one of the main objectives of orthodontic treatment, the aim of the present study was to propose a 3D cephalometric evaluation of the soft tissues of the face. Carrying out the same 3D aesthetic analysis, at the beginning and end of clinical treatment, it is possible to collect information about the influence of orthodontic displacement on the proportions between the diverse areas of the profile.